The Effect of the Genius Learning Strategy Using Flash Cards on Students' Learning Outcomes in Curved Surface Geometry - Norhikmah, Laily; Saputri, Rinda Azmi (Mathematics Education Journal, 2025)
The level of student proficiency in mathematics, especially geometry, was still very low and did not achieve good results. Factors that influenced this included students having difficulty understanding the concepts of the material and the use of inappropriate learning methods. This study aimed to determine the level of learning outcomes in the material of curved side solid shapes using the genius learning strategy with flash card media, as well as the effect of implementing this strategy on mathematics learning outcomes. This type of research was an experiment with a quantitative approach. Data collection techniques included written tests, observation, interviews, and documentation. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests. The results of this study showed that mathematics learning outcomes on the material of curved side solids, by applying the genius learning strategy using flash card media, had an average score of 83.72 in the good category, and there was an influence of the application of the genius learning strategy using flash card media on students' mathematics learning outcomes.